School mathematical discourse in a learning landscape – understanding mathematics education in multicultural settings - Valero, Paola; Meaney, Tamsin; Alrø, Helle; Fairhall, Uenuku; Trinick, Tony (NOMAD Nordic Studies in Mathematics Education, 2008)
By bringing our research work together, we are able to discuss the potential of combining the notions of the learning landscape and school mathematical discourse. We do so in a search for concepts and methodological tools to challenge the simplification of issues in regard to mathematics learning in multicultural settings, when adopting restricted perspectives on issues of bilingualism. In the paper we discuss the relationship between the learning landscape and school mathematical discourse. We then use these notions to analyse two case studies in Danish and New Zealand schools. Our conclusion raises possibilities about how these notions can be used when researching mathematics education in multicultural settings.